60. KNOWLEDGE, PRACTICES AND SOME RELATED FACTORS REGARDING FOOD SAFETY AMONG FOOD HANDLERS AT HOUSEHOLD-BASED FOOD BUSINESSES IN HOC MON DISTRICT, HO CHI MINH CITY IN 2025 (Vietnam Journal of Community Medicine, 2025)
household-based food establishments in Hoc Mon district, Ho Chi Minh city, and to identify related factors.Methods: A cross-sectional descriptive study was conducted in 2025, involving 296 food handlers from household-run food businesses. Data were collected through structured face-to-face interviews and direct observation using a standardized checklist. Descriptive statistics and PR with 95% CI were used to analyze related factors.Results: Overall, 84.5% of respondents demonstrated adequate food safety knowledge, and 82.1% exhibited proper food handling practices. The highest levels of knowledge were related to food poisoning management (91.6%), followed by personal hygiene (88.9%), food preservation (88.9%), waste and environmental hygiene (90.5%), and sourcing and preparation (81.4%). Factors positively related to good knowledge included urban residence (PR = 0.85; 95% CI = 0.78-0.92), higher educational attainment (PR = 1.38; 95% CI = 1.06-1.78), and over two years of work experience (PR = 1.40; 95% CI = 1.24-1.58). Good practices were significantly related to being over 40 years old (PR = 1.17; 95% CI = 1.02-1.35), urban residence (PR = 0.86; 95% CI = 0.78-0.95), and longer work experience (PR = 1.14; 95% CI = 1.01-1.28).Conclusion: Food handlers in household-based establishments in Hoc Mon district generally demonstrated good knowledge and practices regarding food safety. However, targeted interventions are recommended for rural workers, those with lower educational backgrounds, and newly employed food handlers to ensure sustainable improvements in food hygiene and safety.
Keywords: Food safety; household-based food establishments; food handlers; Hoc Mon.